2016
DOI: 10.5194/acp-16-1459-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of nitrate aerosols to ammonia emissions and to nitrate chemistry: implications for present and future nitrate optical depth

Abstract: Abstract. We update and evaluate the treatment of nitrate aerosols in the Geophysical Fluid Dynamics Laboratory (GFDL) atmospheric model (AM3). Accounting for the radiative effects of nitrate aerosols generally improves the simulated aerosol optical depth, although nitrate concentrations at the surface are biased high. This bias can be reduced by increasing the deposition of nitrate to account for the near-surface volatilization of ammonium nitrate or by neglecting the heterogeneous production of nitric acid t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 116 publications
7
109
0
Order By: Relevance
“…Nitrate is simulated in CM3 but is not radiatively active due to its small forcings, as found by previous studies (Naik et al, 2013). However, recent studies have shown that inclusion of nitrate in the radiation scheme improves model AOD (Paulot et al, 2016). Instead of using in-house emissions as in CM2.1 (Horowitz, 2006), the emissions in CM3 were provided by Lamarque et al (2010), an inventory that was compiled for the Climate Model Intercomparison Project Phase 5 (CMIP5) in support of the Intergovernmental Panel on Climate Change's Fifth Assessment Report (AR5).…”
Section: Gfdl Cm3supporting
confidence: 52%
See 1 more Smart Citation
“…Nitrate is simulated in CM3 but is not radiatively active due to its small forcings, as found by previous studies (Naik et al, 2013). However, recent studies have shown that inclusion of nitrate in the radiation scheme improves model AOD (Paulot et al, 2016). Instead of using in-house emissions as in CM2.1 (Horowitz, 2006), the emissions in CM3 were provided by Lamarque et al (2010), an inventory that was compiled for the Climate Model Intercomparison Project Phase 5 (CMIP5) in support of the Intergovernmental Panel on Climate Change's Fifth Assessment Report (AR5).…”
Section: Gfdl Cm3supporting
confidence: 52%
“…5 (Yu et al, 2012). Previous studies have shown that inclusion of nitrate in CM3 considerably improves the seasonal cycle by reducing the contribution of sulfate to AOD in summer while increasing it in winter (Paulot et al, 2016).…”
Section: Comparisons Of Model Data With Observations 421 Regional Cmentioning
confidence: 99%
“…With regard to the predicted increase in NH 3 emissions and the possible compensating effect on aerosol radiative forcing, Paulot et al (2016) emphasize the need to also better constrain the vertical distribution of ammonia. However, there is very little information from measurements on NH 3 at mid-and upper-tropospheric levels.…”
Section: Introductionmentioning
confidence: 99%
“…Managed ecosystems, such as croplands and pasturelands, are the dominant source of ammonia emissions to the atmosphere through emissions from fertilizer and domesticated animals (Erisman et al, 2008). In combination with nitric acid formed from the oxidation of NO x , ammonia can produce ammonium nitrate, an increasingly important source of inorganic PM in regions where sulfur emissions controls substantially reduce sulfate (Paulot et al, 2016;Pinder et al, 2007). The terrestrial biosphere is also a sink of gases and particles.…”
Section: Introductionmentioning
confidence: 99%